Pengukuran Indeks Kepuasan Pasien Forensik Klinik Menggunakan Metode Customer Satisfaction Index - Afandi, Dedi; Arini, Merita (Fakultas Kedokteran Universitas Riau, 2024)
Measuring the patient satisfaction index is essential to establish a baseline for improving service quality in subsequent years. The Customer Satisfaction Index (CSI) method is an effective approach to determine the overall patient satisfaction index over time. At Bhayangkara Hospital Pekanbaru, the satisfaction index of clinical forensic patients has not been previously assessed. This study aims to measure the satisfaction index of clinical forensic patients using the CSI method. A cross-sectional study was conducted on 284 clinical forensic patients at Bhayangkara Hospital Pekanbaru, selected through consecutive sampling. The modified SERVQUAL questionnaire, encompassing five service quality dimensions—reliability, responsiveness, assurance, empathy, and tangibles served as the research instrument. Data were analyzed using the CSI method. The results indicated that the mean overall satisfaction perception was 4.59, with the highest mean observed in the assurance dimension (4.63). Responsiveness was identified as the most important service quality dimension by clinical forensic patients (mean = 4.90). The overall satisfaction index calculated through CSI was 91.2%, indicating a very satisfied level, with the highest satisfaction index in the assurance dimension (92.72%) and the lowest in tangibles (90%). The target for the clinical forensic patient satisfaction index for the coming year should aim to surpass the index obtained in this study.